2014
DOI: 10.7314/apjcp.2014.15.6.2477
|View full text |Cite
|
Sign up to set email alerts
|

Canola Oil Influence on Azoxymethane-induced Colon Carcinogenesis, Hypertriglyceridemia and Hyperglycemia in Kunming Mice

Abstract: Azoxymethane (AOM) is a potent genotoxic carcinogen which specifically induces colon cancer. Hyperlipidemia and diabetes have several influences on colon cancer development, with genetic and environmental exposure aspects. Here, we investigated plasma lipid and glucose concentrations in Kunming mice randomized into four groups; control (no AOM or oil exposure), AOM control, AOM + pork oil, and AOM + canola oil. Aberrant crypt foci (ACF), plasma cholesterol, plasma triglyceride, plasma glucose and organ weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Many signaling pathways are deregulated during the progression of colon cancer (Pandurangan, 2013;Pandurangan and Esa, 2013;Pandurangan and Esa, 2014;). Epidemiological and experimental studies suggest that colon cancer is strongly influenced by nutritional factors, including the amount and composition of dietary fat (Willet et al, 1990;Pandurangan et al, 2013c;He et al, 2014).…”
Section: Luteolin Effects On Colon Cancermentioning
confidence: 99%
“…Many signaling pathways are deregulated during the progression of colon cancer (Pandurangan, 2013;Pandurangan and Esa, 2013;Pandurangan and Esa, 2014;). Epidemiological and experimental studies suggest that colon cancer is strongly influenced by nutritional factors, including the amount and composition of dietary fat (Willet et al, 1990;Pandurangan et al, 2013c;He et al, 2014).…”
Section: Luteolin Effects On Colon Cancermentioning
confidence: 99%
“…He et al, 2014 observed that in Kunming mice exposed to AOM plus canola oil had a strong inhibitory effect of AOM-induced colorectal carcinogenesis. On the other hand, in an 8-year epidemiological study, olive oil (contained in fried foods) was found to protect against the development of colon cancer (Galeone et al, 2007).…”
Section: Discussionmentioning
confidence: 96%
“…Azoxymethane (AOM) is a potent carcinogen for colon and liver (He, Cichello, Duan, & Zhou, ; Nakanishi, Kataoka, Kuwahara, & Ohnishi, ). Hepatotoxic effects were also shown in animal models (Khurana, Shah, & Twaddell, ).…”
Section: Introductionmentioning
confidence: 99%
“…The protective effects of several food ingredients have been studied against AOM's hepatotoxic effects (He et al., ). The human body has various antioxidants as a defence mechanism, some of which are dietary‐derived (Catoni, Peters, & Schaefer, ; Ruiz, Egea, Tomas‐Barberan, & Gil, ).…”
Section: Introductionmentioning
confidence: 99%